(untitled) (Gremium, 2015)
This paper analyzes the different roots of current residential high-rise clusters emerging in new city districts along the coast of Bahrain’s capital city Manama, and the resulting urban planning and design challenges. Since the local real-estate markets were liberalized in Bahrain in 2003, the population grew rapidly to more than one million inhabitants. Consequently, the housing demand increased rapidly due to extensive immigration. Many residential developments were however constructed for the upper spectrum of the real-estate market, due to speculative tendencies causing a raise in land value. The emerging high-rise clusters are developed along the various waterfronts of Manama on newly reclaimed land. This paper explores the spatial consequences of the recent boom in construction boom and the various challenges for architects and urban planners to enhance urban qualities.